The Good, the Bad, and the Ugly: Fault Lines in Ecofeminism - Jabeen, Neelam (Pakistan Journal of Humanities and Social Sciences, 2023)
Women’s association with nature has been debated for long now. Some have moved beyond this debate and have started to look at the repercussions of this assemblage more than its reasons. In this paper, I use a South-Asian/postcolonial text to show that there are fault lines within women-nature assemblage. Pertaining to the study of women-nature connection in literature, there are limited representations that are studied and theorized: a) women as showing care and compassion for nature and life in general, or showing a lack thereof owing to internalized patriarchy, or their material circumstances; b) women and nature being oppressed by androcentrism; c) women in biomorphic unity with nature. In literature, when women are shown in biomorphic unity with nature, the depiction is usually that of a pleasant natural environment where women are shown to be one with nature. What is least studied and lacks theorization is that women-nature connection where neither women nor nature is in its best form. I call it bad-women-bad-nature connection.